1990
DOI: 10.1002/mrm.1910150308
|View full text |Cite
|
Sign up to set email alerts
|

Signal‐to‐noise in phase angle reconstruction: Dynamic range extension using phase reference offsets

Abstract: The dynamic range of phase-reconstructed magnetic resonance images is compared to that of magnitude-reconstructed images. From analysis of propagation of errors, the phase angle noise is phase-independent and given in radians by sigma ([I])/[I], the noise-to-signal ratio of the corresponding magnitude-reconstructed image. As the phase can range from minus pi to pi, the phase angle dynamic range is 2 pi times that of the signal magnitude. These results agree with experiment, verifying that the noise in the two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
146
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(152 citation statements)
references
References 38 publications
(18 reference statements)
2
146
0
Order By: Relevance
“…In this step, all the noiseless signal was placed in the real channel, as allowed because of the phase independence of magnitude-reconstructed noise as suggested 64 and derived. 71 Finally, independent noise fluctuations were added to M copies of the noiseless DT-MRI data to generate M frames of noisy DT-MRI images, which were then averaged to simulate the DTT experiment (M = 10 for the standard case).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this step, all the noiseless signal was placed in the real channel, as allowed because of the phase independence of magnitude-reconstructed noise as suggested 64 and derived. 71 Finally, independent noise fluctuations were added to M copies of the noiseless DT-MRI data to generate M frames of noisy DT-MRI images, which were then averaged to simulate the DTT experiment (M = 10 for the standard case).…”
Section: Resultsmentioning
confidence: 99%
“…The behavior of g as a function of r and i was simulated 44 assuming that e r and e i are independent and uncorrelated, as is the case for MR thermal noise. 71 These simulations determined that g decreases from 0.786 as r and i deviate from equality, so that g can be used to verify that r = i in the magnitude DT-MRI data.…”
Section: Appendix: Noise Analysis Of Dt-mri Images and Use In Simulatmentioning
confidence: 94%
See 2 more Smart Citations
“…Conturo et al (14) have demonstrated that the phase error is inversely proportional to the signal-to-noise ratio (SNR) of the complex MR image, i.e. ( ) ϭ (|I|)/|I| ϭ 1/SNR, where I and (|I|) represent the intensity and the noise level of the magnitude image, respectively.…”
Section: Theorymentioning
confidence: 99%